Utveckling av metod för utvärdering av synnervens funktion hos häst - Ström, Lena (2004)
VEP, visual evoked potential is an electrophysiologic test that can be used for evaluating the higher visual pathways. The aim of this study was to investigate if it is possible to adapt this method to horses. This method could have a clinical use in addition to the existing diagnostic methods that are available to evaluate vision in horses.